2014
DOI: 10.1186/preaccept-1453408941291432
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and correlates of adherence to combination antiretroviral therapy (ART) for chronic HIV infection: a meta-analysis

Abstract: Background: Adherence to combination antiretroviral therapy (ART) is a key predictor of the success of human immunodeficiency virus (HIV) treatment, and is potentially amenable to intervention. Insight into predictors or correlates of non-adherence to ART may help guide targets for the development of adherence-enhancing interventions. Our objective was to review evidence on predictors/correlates of adherence to ART, and to aggregate findings into quantitative estimates of their impact on adherence. Methods: We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
174
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(192 citation statements)
references
References 228 publications
11
174
2
5
Order By: Relevance
“…Given the changes in morbidity and mortality, studies have shown the positive impact of adherence to antiretroviral therapy on the quality of life. (5,13,14) Permeated by feelings of guilt, loneliness and fear of death, participants who exercised spirituality by means of faith or religious beliefs achieved better coping with the HIV serostatus, encouragement and ability to work. Spirituality and religion improve health, quality of life, and help people living with HIV to cope with stress from stigma and discriminatory practices.…”
Section: Discussionmentioning
confidence: 99%
“…Given the changes in morbidity and mortality, studies have shown the positive impact of adherence to antiretroviral therapy on the quality of life. (5,13,14) Permeated by feelings of guilt, loneliness and fear of death, participants who exercised spirituality by means of faith or religious beliefs achieved better coping with the HIV serostatus, encouragement and ability to work. Spirituality and religion improve health, quality of life, and help people living with HIV to cope with stress from stigma and discriminatory practices.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a secondary analysis of data collected for other purposes and which contained a substantial number of research participants with missing data. We relied on self-reported adherence barriers, which may be prone to recall and social desirability bias and may not have fully captured all adherence barriers (e.g., substance use, 47 trust in HIV care provider, pregnancy, 36,48 etc.). We examined adherence barriers at only one time point early in the ART course.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified several factors as potentially contributing to late presentation, poor HAART uptake and low retention in HIV care. These factors include stigma, fear of status disclosure, complexity of treatment regimens and lack of psychosocial support (48); lack of confidentiality and fear of discrimination at health facilities, workplace and community (49); poor staff-patient relationships and underestimation of the need for HAART (50); and active drug use (43,46). Stigma and fear of disclosure are particularly important among females living in a conservative society.…”
Section: Discussionmentioning
confidence: 99%